Evaluation of reaction kinetics for the catalyst used in PCRD and study of channel affect on the same. (18th March 2020) - Shukla, Vikram; Tyagi, Deepak; Varma, Salil; Saha, B.; Shirsat, A.N.; Ganju, Sunil; Sengupta, S.; Bhattacharya, S.; Maheshwari, N.K.
Abstract: Hydrogen mitigation strategies have gained importance for Nuclear reactors owing to damage caused to integrity of reactor containment by hydrogen fire in three major nuclear accidents of Three Miles Island, Chernobyl and Fukushima. One promising technology for hydrogen mitigation is deploying Passive Catalytic Recombiner Devices (PCRDs). Principle involved here is recombining hydrogen released during accident with oxygen from ambient air inside reactor containment on catalyst surface to form steam. Present work focuses on experimental evaluation of reaction kinetics associated with hydrogen-oxygen recombination on surface of indigenous PCRD catalyst developed for Indian Nuclear Power Plants. Behavior of catalyst plates stacked in parallel inside PCRD has also been evaluated. This effect is due to difference in migration mechanisms of reactants and products to and from the catalyst surface. Overall affect has been empirically approximated as single step Arrhenius equation. This is significant in modelling of PCRDs for faster containment analysis using CFD. Highlights: Kinetics of indigenous PCRD catalyst for Indian NPP has been experimentally studied. Behavior of catalyst plates stacked in parallel inside PCRD has also been evaluated. Variation in migration mechanism of reactants to catalyst surface affects behavior. Overall affect has been empirically approximated as single step Arrhenius equation. This is significant in modelling of PCRDs for faster containment analysis using CFD.